1984
DOI: 10.1002/fut.3990040206
|View full text |Cite
|
Sign up to set email alerts
|

The optimal hedge ratio in unbiased futures markets

Abstract: n extensive body of recent research in futures markets has dealt with the A determination of the minimum variance hedging ratio.' The strength of these results is mitigated, however, by two factors: First, the researchers assume (implicitly or explicitly) that the hedger has a quadratic utility function. This is well-known to be a problematic assumption, since quadratic utility functions have many undesirable properties.2 Second, the hedge ratio which is determined is not an optimal hedge ratio, but rather one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 12 publications
3
57
0
Order By: Relevance
“…It is equal to 1.29 for the selected farm in Centre and to 0.68 for the selected farm in Ile de France. 12 If there was no production risk, the optimal unbiased futures hedge ratio would thus reduce to the beta coefficient, a well known result in the optimal hedging literature (see, for example, Benninga, Eldor and Zilcha, 1984). Table 3 shows the optimal hedge ratios under alternative insurance policies when futures markets are perceived as unbiased, i.e., f E F= .…”
Section: Optimal Hedging Decisionsmentioning
confidence: 92%
“…It is equal to 1.29 for the selected farm in Centre and to 0.68 for the selected farm in Ile de France. 12 If there was no production risk, the optimal unbiased futures hedge ratio would thus reduce to the beta coefficient, a well known result in the optimal hedging literature (see, for example, Benninga, Eldor and Zilcha, 1984). Table 3 shows the optimal hedge ratios under alternative insurance policies when futures markets are perceived as unbiased, i.e., f E F= .…”
Section: Optimal Hedging Decisionsmentioning
confidence: 92%
“…When investors maximize expected utility of portfolio returns, the optimal hedge ratio can be obtained by using the mean-variance (MV) model since, as shown by Levy and Markowitz [9], MV approximates expected utility, regardless of the utility and the probability distribution. Furthermore, Benninga, Eldor and Zilcha [10,11] showed that the optimal hedge ratio is equal to the minimum-variance hedge ratio which is:…”
Section: The Portfolio Insurance Model With Index Put Optionsmentioning
confidence: 99%
“…Expression (10), on its part, states that the insurance net payoff should itself equal its risk premium. Indicating with the sign * the vectors and the submatrices corresponding to non zero activities, and applying the variance and covariance definitions, we can write: of total revenue per ha of the area i olved i the scheme and the corresponding mean according to the so called "regressability assumption" (Benninga et al, 1984): Going ba to the maximizing conditions, expression (11) states that prices of all non zero activities should equal marginal costs at the optimum, while expression (12) indicates that the quantity of insurance acquir ck ed by the i-th firm equals the net value of the insurance, including its utility from risk diversification. This result can be seen more clearly, dropping the asterisks for simplicity, by writing it as follows:…”
Section: The Competitive Market Modelmentioning
confidence: 99%